Using low-cost air quality sensors to estimate wildfire smoke infiltration into childcare facilities in British Columbia, Canada - Michael Joseph Lee; James M Dickson; Ophir Greif; William Ho; Sarah B Henderson; Gary Mallach; Eric S Coker (IOP Publishing, 2024)
The health risks associated with wildfires are expected to increase due to climate change. Children are susceptible to wildfire smoke, but little is known about indoor smoke exposure at childcare facilities. The objective of this analysis was to estimate the effects of outdoor PM _2.5 and wildfire smoke episodes on indoor PM _2.5 at childcare facilities across British Columbia, Canada. We installed low-cost air-quality sensors inside and outside 45 childcare facilities and focused our analysis on operational hours (Monday-Friday, 08:00-18:00) during the 2022 wildfire season (01 August-31 October). Using random-slope random-intercept linear mixed effects regression, we estimated the overall and facility-specific effects of outdoor PM _2.5 on indoor PM _2.5 , while accounting for covariates. We examined how wildfire smoke affected this relationship by separately analyzing days with and without wildfire smoke. Average indoor PM _2.5 increased by 235% on wildfire days across facilities. There was a positive relationship between outdoor and indoor PM _2.5 that was not strongly influenced by linear adjustment for meteorological and area-based socio-economic factors. A 1.0 μ g m ^−3 increase in outdoor PM _2.5 was associated with a 0.55 μ g m ^−3 [95% CI: 0.47, 0.63] increase indoors on non-wildfire smoke days and 0.51 μ g m ^−3 [95% CI: 0.44, 0.58] on wildfire-smoke days. Facility-specific regression coefficients of the effect of outdoor PM _2.5 on indoor PM _2.5 was variable between facilities on wildfire (0.18-0.79 μ g m ^−3 ) and non-wildfire days (0.11-1.03 μ g m ^−3 ). Indoor PM _2.5 responded almost immediately to increased outdoor PM _2.5 concentrations. Across facilities, 89% and 93% of the total PM _2.5 infiltration over 60 min occurred within the first 10 min following an increase in outdoor PM _2.5 on non-wildfire and wildfire days, respectively. We found that indoor PM _2.5 in childcare facilities increased with outdoor PM _2.5 . This effect varied between facilities and between wildfire-smoke and non-wildfire smoke days. These findings highlight the importance of air quality monitoring at childcare facilities for informed decision-making.